PENGARUH FAKTOR-FAKTOR AFEKTIF TERHADAP KEBERHASILAN BELAJAR ENGLISH FOR MANAGEMENT (ENGLISH FOR SPECIFIC PURPOSES) DALAM ERA DISRUPSI - Ida Nyoman Basmantra; Putu Ratna Juwita Sari (Institut Pariwisata dan Bisnis Internasional, 2019)
The study aimed at investigating the level of some affective factors which influenced the English for Management Learning Achievement; and uncovering how, psychologically, those factors were felt by the students. The study had been carried out in three steps; first, theoretical and empirical study on affective factors yielded in six factors; second, data collection on those factors through questionnaires, and third, focused group discussion (FGD). The study applied mixed methods of data collection and analysis. Quantitative method using t test was applied to determine the level of determination of the six affective factors upon above average and low average students, respectively. Qualitative method was applied through FGD and descriptive analysis. The results of the anÃ¡lisis show that the level of anxiety and learned helplessness of the above average students is lower than of the below average ones; while the level of self efficacy, locus of control, interest, dan integrativeness of the above average students is higher than of the below average ones. For the above average students, low level of anxiety and learned helplessness supports learning, and high level of self-efficacy, locus of control, interest, dan integrativeness is a bid modality for their success. The below average students, however, tend to be stucked by high level of anxiety and learned helplessness which hinders their learning.